MEDIA PUL (POP UP LARGE) BERBASIS AUDIO DENGAN PEMANFAATAN LIMBAH KERTAS SEBAGAI OPTIMALISASI PENDIDIKAN BERETIKA PADA SISWA SEKOLAH DASAR - Reza Syehma Bahtiar; Desi Eka Pratiwi (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2018)
This research was conducted as a means of optimizing character education of elementary school students through PUL (Pop Up Large) media. This matter is basically associated with the reality that the elementary school students nowadays are able to make use of technology advancement, such as cellphone with sophisticated features along with easy internet access, yet they do not use it appropriately. The Curriculum 2013 focuses on teaching and learning activities for students (Student Center), accordingly, the students are required to be active in teaching and learning activities, in addition students are expected to have good ethics of public facilities in the surrounding environment. The lack of knowledge and insight towards the public facility around them has an impact on their unconcerned attitude. One type of media that is able to answer the problem is by using the PUL (Pop Up Large) media. This research used qualitative method, kuesioner was used as data collection techniques. The instrument for collecting data is kuesioner guidelines Data analysis was done descriptively using data analysis technique from Miles and Huberman model. The data analysis phase includes data reduction, display data, and conclusion drawing / verification. The results showed that the implementation of PUL (Pop Up Large) media in elementary school students can improve the understanding of character education optimally.